Analisis Terhadap Penetapan Nilai Ganti Untung Pengadaan Tanah untuk Kepentingan Umum dalam Pembangunan Jalan Tol - Suhartoyo Suhartoyo; sako Iqsal Madani (Administrative Law Department, Faculty of Law, Universitas Diponegoro, 2021)
Abstract This journal aims to analyze the determination of replacement value in land acquisition for the public interest with a case study on the construction of the toll road. The appraisal team determines the replacement value in land acquisition for public use by taking into account the physical and non-physical values in accordance with Law No.2 of 2012 and the Indonesian Appraisal Standard. Obstacles in the implementation of providing compensation in land acquisition for the construction of the Semarang-Demak toll road are obstacles that arise from the community holding rights to land, buildings and plants and objects related to land, lack of public awareness to participate in development and lack of awareness. understanding of the meaning of the public interest, the social function of land rights, lack of understanding of the plans and objectives of the project development, which previously provided explanation and counseling from the Land Acquisition Committee for the construction of t Toll Road. There are still people who feel dissatisfied, especially regarding the market value of land, this is because people think that their land is the same as other land why the market value of the land is different. Keywords: Land acquisition; Land Appraisal; Toll Road Abstrak Jurnal ini bertujuan untuk menganalisis penetapan nilai pengganti dalam pembebasan tanah untuk kepentingan umum dengan studi kasus pada pembuatan jalan tol . Penetapan nilai pengganti dalam pembebasan tanah untuk kepentingan umum dilakukan oleh tim appraisal dengan memperhatikan nilai fisik dan nilai non fisik sesuai dengan UU No 2 tahun 2012 dan Standar Penilaian Indonesia. Hambatan-hambatan dalam pelaksanaan pemberian ganti kerugian dalam pengadaan tanah untuk pembangunan tol Semarang-Demak adalah hambatan yang berasal dari masyarakat pemegang hak atas tanah, bangunan dan tanaman serta benda- benda yang berkaitan dengan tanah, kurangnya kesadaran masyarakat untuk berperan serta dalam pembangunan dan kurang pemahaman terhadap arti kepentingan umum, fungsi sosial hak atas tanah, kurangnya pemahaman mengenai rencana dan tujuan pembangunan proyek tersebut yang sebelumnya telah dilakukan penjelasan dan penyuluhan dari Panitia Pengadaan Tanah untuk pembangunan Tol . Masih ada saja masyarakat yang merasa kurang puas, terutama mengenai nilai pasar tanah, hal ini dikarenakan masyarakat beranggapan bahwa tanah mereka sama dengan tanah yang lain kenapa nilai pasar tanahnya berbeda. Kata Kunci: Pembebasan Tanah; Penilaian Tanah; Pembangunan Jalan Tol